Land use/cover and landscape pattern changes in Manas River Basin based on remote sensing - Li, Xiaolong; He, Xinlin; Yang, Guang; Liu, Hongguang; Long, Aihua; Chen, Fulong; Liu, Bing; Gu, Xinchen (International Journal of Agricultural and Biological Engineering, 2020)
Large-scale water and soil development in inland river basins in arid areas has made changes in landscape composition and structure, threatening the ecological balance. In order to study the trend of land use/cover and landscape pattern change and its relationship with water resources utilization in Manas River Basin, the land-use data of five periods in 1976, 1990, 2000, 2010 and 2015 were analyzed. The results showed that: (1) During 1976-2015, farmland and construction land continuously increased, forest land and grassland continuously decreased, the water area initially reduced and then increased, the area of saline-alkali land initially increased and then reduced, the overall trend of unused land and the sandy area was decreasing and the area of different time periods is floating. The areas of land-use types either increased or decreased. This indicates that the landscape pattern of the basin changes dramatically, and human activities are the main reasons for this phenomenon; (2) The oasis area increased from 3480.2 km2 in 1976 to 7982.0 km2 in 2015, with an obvious increasing trend. The oasis area clearly increased during 1976-1990, the growth rate was 40.6%, the growth rate of the oasis area was 129.4%. In the last 40 years, the degree of desertification fluctuated and decreased. The increase of the oasis area directly leads to the increase of water resources utilization and aggravates the degree of water resources shortage; (3) The pattern of land-use types showed a non-equilibrium trend. In the region with increasing landscape heterogeneity, the overall landscape pattern was increasingly controlled by the majority of patches. The intensive land management model and drip irrigation under mulch have improved the utilization efficiency of water resources and saved water resources from engineering renovation and irrigation management.Keywords: arid area, Manas River Basin, land use/cover change, landscape pattern, remote sensing, driving forceDOI: 10.25165/j.ijabe.20201305.4783Citation: Li X L, He X L, Yang G, Liu H G, Long A H, Chen F L, et al. Land use/cover and landscape pattern changes in Manas River Basin based on remote sensing. Int J Agric & Biol Eng, 2020; 13(5): 141–152.